Validity Test and Practicality Test of Virtual Reality Based Learning Media on Optical Equipment Material - Saydah, Ayita; Fakhruddin Z, Fakhruddin Z; Irianti, Mitri; M. Nor, M. Nor (Journal of Educational Sciences, 2024)
One of the physics materials that is included in the abstract category is optical devices, especially the process of light entering the eye through a lens that cannot be seen directly by humans. The use of learning media combined with virtual reality is an alternative problem by providing visualization of material that becomes concrete in 3D or can be seen in 360°, making it easier for teachers and students in the learning process. This research aims to determine the feasibility of virtual reality-based learning media for optical devices in order to increase understanding of concepts in optical equipment, especially eyes and glasses. Validity testing is carried out by validating the learning media by experts and practicality testing is carried out by testing the media on teachers and high school students. The results of the research show that the average value of the validity test for virtual reality-based learning media reached 87% with valid criteria and while the practicality test by teachers and students obtained an average score of 90% by teachers and 89% by students with practical criteria so that the media Virtual reality-based learning is suitable for use to help the learning process in schools. Based on the validity and practicality analysis, the media can be used in real learning processes and can be tested further regarding its effectiveness.